A Long Term Follow Up to a Randomized Controlled Trial of Comprehensive Behavioral Intervention for Tics - (:unkn) unknown (My University, 2015)
Tourette Syndrome (TS) is a neuropsychiatric disorder characterized by stereotyped involuntary movements called tics. Tics can be movements or sounds and usually present first during childhood. Although tics may wax and wane throughout life, few long-term follow up studies of tic disorders have been conducted. In the past decade, behavior therapy has become a promising treatment for individuals with TS. Studies on behavior therapy for tics show favorable results at post treatment, but no studies have examined the long-term effects of such treatments beyond 10 months. The current study aimed to address this lack of research by conducting assessments with a group of adolescents and young adults who participated in a randomized controlled trial (RCT) of behavior therapy for tic disorders over six years ago. Results from 15 subjects indicated tics decreased in severity into late adolescence and adulthood and treatment gains were maintained between post treatment and follow up. These effects were even more pronounced for the group traditionally assigned to behavior therapy. Many of the predictors of long-term tic severity identified in the literature did not predict tic severity or general functioning at follow up, and there were no significant differences between baseline and follow up scores on measures related to other psychological and behavior problems. Subjects also reported how long they continued using various treatment components and which strategies were more helpful than others. Implications for future studies on the course of tic disorders and treatment follow-up assessments are discussed.
Keywords: Behavior Therapy; Long Term Outcomes; Tic Disorders; Tourette Syndrome